Training report: capacity building in entrepreneurial and business skills for operationalizing fresh cassava roots packhouse. - Nyamutoka, P.; Wanda, K.; Kwagala, I.; Muyinza, H.; Kaliisa, R.; Menya, G.; Nuwamanya, E.; Nyakaisiki, E.; Nanyondo, R.; Abass, A.; Matovu, Moses (2017)
This report describes the capacity building process and activities that were done to enhance the business and entrepreneurial skills of packhouse operators.